Toward an Integrative Paradigm of Islamic Education: Bridging Classical Islamic Thought and Modern Educational Values - Tamimi, Ahmad Ishom (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study examines the transformation of Islamic educational values from classical foundations to their contemporary implementation within modern educational institutions in the Islamic world and Indonesia. Employing a qualitative literature review, the analysis explicitly traces both continuity and the paradigm shift in Islamic education by critically synthesizing empirical findings from peer-reviewed journals and institutional reports. The analysis demonstrates that, while classical Islamic education was grounded in the unity of knowledge (tawḥīd al-‘ilm) and moral cultivation (tarbiyah al-akhlaq), modern Islamic educational institutions reinterpret these principles to address scientific, technological, and socio-cultural challenges. The central finding of this study is the identification and formulation of a conceptual model of integrative Islamic education, which constitutes the article’s main contribution. This model is structured around four interrelated pillars: epistemological unity, contextual curriculum design, value-internalizing pedagogy, and institutional sustainability. These pillars provide a coherent framework that explains how religious and scientific disciplines can be integrated within a unified epistemological and pedagogical structure. The proposed model offers a conceptual reference for future curriculum development and educational policy in the context of global Islamic education.